Experimental Study of the Lateral Spreading Pressure Acting on a Pile Foundation During Earthquakes - Nagao, T.; Shibata, D. (Engineering, Technology & Applied Science Research, 2019)
In the seismic design of pile foundations, the safety of the pile is assessed by considering the inertial force during an earthquake and subgrade reaction as external forces against the pile. The amount of deformation of the pile must be limited to a small value to maintain the safety of the pile. In the event of a large earthquake, quay walls and seawalls are subjected to lateral spreading because of the influence of biased seaward earth pressure. The amount of lateral spreading is considerably larger than what can be expected in a typical pile seismic design and may reach several meters. In this study, loading experiments that reproduced lateral spreading were conducted to evaluate the lateral spreading pressure acting on a pile when considerably large lateral spreading occurred. The experiment results showed that lateral spreading pressure depended on the ratio of pile spacing to pile diameter while the peak value of lateral spreading pressure was larger than the one assumed in practical design.